Rising trend of oral cancers in India: a comprehensive review - Tali, Tavseef Ahmad; Bashir, Mustafa; Ashraf, Bilkees; Teli, Toufeeq Ahmed; Amin, Fiza (International Journal of Research in Medical Sciences, 2025)
Oral cancer, encompassing malignancies of the lip, tongue, buccal mucosa and oropharynx, is a major public health concern in India, accounting for approximately one-third of the global burden with 77,000 new cases and 52,000 deaths annually. This comprehensive review examines the rising trend of oral cancers in India, focusing on epidemiology, risk factors, clinical characteristics, diagnostic challenges, management strategies and preventive approaches. The age-standardized incidence rate is 10.4 per 100,000, with higher prevalence among men and in regions like Uttar Pradesh, Bihar and the north eastern states. Key risk factors include tobacco use (smoked and smokeless), betel quid chewing, alcohol consumption, HPV infection and genetic predispositions, with squamous cell carcinoma dominating (>90% of cases). Advanced-stage diagnosis, limited access to screening and advanced diagnostics and reliance on Western treatment protocols contribute to poor outcomes. Preventive strategies, such as tobacco cessation, HPV vaccination and community-based screening, show promise in reducing incidence. This review emphasizes the need for region-specific research, affordable diagnostics and enhanced healthcare infrastructure to address the growing burden of oral cancers in India.